The role of the genetic elements bla oxa and IS Aba 1 in the Acinetobacter calcoaceticus-Acinetobacter baumannii complex in carbapenem resistance in the hospital setting - Kobs,Vanessa Cristine (2016)
Abstract: INTRODUCTION: Members of the Acinetobacter genus are key pathogens that cause healthcare-associated infections, and they tend to spread and develop new antibiotic resistance mechanisms. Oxacillinases are primarily responsible for resistance to carbapenem antibiotics. Higher rates of carbapenem hydrolysis might be ascribed to insertion sequences, such as the ISAba1 sequence, near bla OXA genes. The present study examined the occurrence of the genetic elements bla OXA and ISAba1 and their relationship with susceptibility to carbapenems in clinical isolates of the Acinetobacter calcoaceticus-Acinetobacter baumannii complex. METHODS: Isolates identified over 6 consecutive years in a general hospital in Joinville, Southern Brazil, were evaluated. The investigation of 5 families of genes encoding oxacillinases and the ISAba1 sequence location relative to bla OXA genes was conducted using polymerase chain reaction. RESULTS: All isolates presented the bla OXA-51-like gene (n = 78), and 91% tested positive for the bla OXA-23-like gene (n = 71). The presence of ISAba1 was exclusively detected in isolates carrying the bla OXA-23-like gene. All isolates in which ISAba1 was found upstream of the bla OXA-23-like gene (n = 69) showed resistance to carbapenems, whereas the only isolate in which ISAba1 was not located near the bla OXA-23-like gene was susceptible to carbapenems. The ISAba1 sequence position of another bla OXA-23-like-positive isolate was inconclusive. The isolates exclusively carrying the bla OXA-51-like gene (n = 7) showed susceptibility to carbapenems. CONCLUSIONS: The presence of the ISAba1 sequence upstream of the bla OXA-23-like gene was strongly associated with carbapenem resistance in isolates of the A. calcoaceticus-A. baumannii complex in the hospital center studied.